Does composite repair of giant paraoesophageal hernia improve patient outcomes?. Issue 3 (8th November 2020) - Lee, Felix; Khoma, Oleksandr; Mendu, Maite; Falk, Gregory
Abstract: Background: Paraoesophageal hernia (PEH) is often symptomatic and reduces patients' quality of life (QoL). There is ongoing debate regarding the most effective surgical technique to repair giant PEH. This study aimed to see if an elective laparoscopic non‐mesh composite technique of giant PEH repair offered an advantage in symptom control, hernia recurrence, QoL, morbidity and mortality. Methods: Data were extracted from a prospectively maintained database of patients undergoing hiatal hernia repair. Composite hernia repairs from inception for giant PEH between March 2009 and December 2015 were included. Perioperative mortality, complications, hernia recurrence rates, prevalence, recurrence of symptoms and QoL were included in analysis. Results: Inclusion criteria were met by 218 patients. Mean age was 70 (49–93). The average hernia size was 62% (range 30–100%; SD 21). There was one perioperative death and three significant complications (Clavien–Dindo grade III and IV). Recurrence rate was 24.8%. Without recurrence, QoL improved significantly across all domains. Recurrence of hiatus hernia reduced QoL. Surgery resulted in resolution of symptoms other than dysphagia which was incompletely improved. Patients' overall satisfaction with surgery was high. Conclusion: Composite repair of giant PEH is safe with overall good outcomes. Majority of hernia recurrence are small and asymptomatic. Hernia recurrence negatively affected long‐term QoL scores. Abstract : This prospective cohort study of 218 patients examines outcomes of composite repair of giant paraoesophageal hernia. Composite repair provided excellent symptom control with complication and recurrence rates comparable with other techniques. Recurrence was associated with worse symptom control and no improvement in long‐term quality of life scores.